ANALISIS TREN DAN PERKEMBANGAN TESIS BIDANG TEKNOLOGI PENDIDIKAN UNIVERSITAS SEBELAS MARET MENGGUNAKAN TEKNIK SCIENCE MAPPING - Hardian Satiawardana, Tri; Nugroho, Eko (BACA: Jurnal Dokumentasi dan Informasi, 2019)
This research purpose is to track scientific trend and development of master thesis in the UNS Educational Technology study program. The novelty of this research is the combination of science mapping and and linear regression approach to analysis centrality in determining scientific trend from 2012 until 2017. In this research, science mapping combines co-word analysis represented by the master thesis keywords and social network analysis through degree, betweenness, closeness and PageRank centrality. General outlook, the development of relations between clusters and keywords and centrality from year to year will be analyzed using Gephi software. To get representative maps, the map be organized using the Fruchterman-Reingold and Circular layout algorithms. To determine the trend of research focus, all four centralities will be analyzed using Tableau software. The study found that within six years, the focus of research was dominated by topics related to the evaluation of learning methods that emphasized cognitive aspects, had a contextual approach, cooperative and utilized interactive multimedia technology. It was also found that there was a shift in research from conventional learning media to information technology-based since 2015 and the emergence of new scientific topics since 2017. The future scientific trend is the development of interactive, contextual, cooperative learning strategies and utilizing information technology-based learning media.